The strategic response of full service airlines to the low cost carrier threat and the perception of passengers to each type of carrier - O'Connell, John F. (Cranfield University, 2007)
Low cost carriers have changed the competitive dynamics of the short-haul market forever. They have revolutionised the way of doing business in aviation by adopting a fresh approach on both strategic and operational issues. Simplicity has become their universal principle over network airlines and subsequently they have achieved substantial cost advantages which are passed onto the consumer as lower fares. Network airlines have found it difficult to reshape their structural barriers and have been slow to incorporate the components that low cost carriers deemed very significant in impacting their operating margins. However, a restructuring of their internal weaknesses should spur initiatives to design long-term strategies to address those shortcomings. Network airlines rely on producing value-adding and consumerdriven product differentiation beyond the basics of the low cost carrier product. To further differentiate themselves network airlines need to focus on: customer satisfaction; develop long term mutually beneficial relationships with both passengers and corporations; collaborate with a wide range of bipartisan partners; retain differentiated flight products that add value; and to incorporate strategies that other network carriers deemed paradigmatic. Network carriers should resist reducing costs associated with value-added services and need to become innovative in generating alternative revenue streams.